EFFECT OF MARKETING STRATEGY ADAPTATION ON KNOWLEDGE EXPLOITABILITY - Nurcholis, Lutfi (Universitas Brawijaya, Indonesia, 2018)
The objectives of this research is establishing a theoretical model to explain the effect of marketing strategy adaptation on knowledge exploitability. The research is a modeling approach, by using the library and literature method. Besides that, the study employs the theoretical study to strengthen the relationships among the founded concepts.The results of this study are propositions formulated in the form of basic theoretical models and developed in the form of hypotheses and empirical models of research.This research conducted at Batik's SME in Pekalongan Indonesia. The sample determined by purposive sampling. The total respondent from this research is 100 respondents. The results from regression analysis with SPSS, and hypotheses testing by t-test are as follows:new market exploration, product diversity and marketing program developmenthas significant positive influence toward knowledge exploitability.